The triangular relationship between audit committee characteristics, audit input and financial reporting quality - KIM, Jae Bum (Institutional Knowledge at Singapore Management University, 2012)
Using the reforms to audit committees mandated by the Sarbanes-Oxley Act of 2002 and the difference-in-difference approach, we examine the impact of changes in audit committee attributes (financial expertise, size and independence) on the corporate commitment to audit assurance and on the likelihood of financial statement restatements. Firms that were directly affected by the reforms experienced a greater improvement in audit inputs (measured by audit fees and the appointment of an industry specialist auditor) and a larger decline in financial statements restatements relative to firms that had already been compliant. Importantly, we find that the decline in restatements is not related to the improvement in audit inputs. This suggests that larger, more independent and more competent audit committees are able to better detect misstatements or to deter opportunistic reporting by management, independent of the level of the audit input quality. The results therefore provide justification for the audit committee reforms.